What Counts as Credible Evidence in Applied Research and Evaluation Practice? - Jason T. Burkhardt; Jan K. Fields (The Evaluation Center at Western Michigan University, 2010)
A review of the book What Counts as Credible Evidence in Applied Research and Evaluation Practice? by Stewart I. Donaldson, Christina A. Christie, & Melvin M. Mark, published in 2008 by Sage.